2016
DOI: 10.1111/acer.13233
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure and Pair Feeding Differentially Impact Puberty and Reproductive Development in Female Rats: Role of the Kisspeptin System

Abstract: Background Reproductive maturation is initiated with the onset of puberty, which activates the hypothalamic-pituitary-gonadal axis and coincidences with increased expression of the hormone kisspeptin within the hypothalamus. Maturational events are sensitive to environmental factors, including alcohol, which is known to delay reproductive development. We hypothesized that, similar to alcohol's adverse effects during reproductive maturation, prenatal alcohol exposure (PAE) would alter pubertal markers, sex horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…This ensured that the control group received the same daily caloric intake per body weight as a 'yoked' PAE dam, thus allowing the effects of the liquid diet alone to be disassociated from the specific effects of the EtOH. In some cases, the EtOH was replaced with sucrose (Boggan et al 1979, McGivern & Yellon 1992, 1995, Blanchard & Hannigan 1994 or maltose-dextrin (Udani et al 1985, Esquifino et al 1986, Lan et al 2009, Murugan et al 2013, Sliwowska et al 2016), but in some cases, there was nothing added to substitute for the EtOH (McGivern 1987, Polanco et al 2010, 2011, even though these studies classified their control as 'pair fed'. Chen and Smith (1979) delivered the EtOH in a saccharin solution to treated animals, but controls only received water.…”
Section: Details Of Control Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…This ensured that the control group received the same daily caloric intake per body weight as a 'yoked' PAE dam, thus allowing the effects of the liquid diet alone to be disassociated from the specific effects of the EtOH. In some cases, the EtOH was replaced with sucrose (Boggan et al 1979, McGivern & Yellon 1992, 1995, Blanchard & Hannigan 1994 or maltose-dextrin (Udani et al 1985, Esquifino et al 1986, Lan et al 2009, Murugan et al 2013, Sliwowska et al 2016), but in some cases, there was nothing added to substitute for the EtOH (McGivern 1987, Polanco et al 2010, 2011, even though these studies classified their control as 'pair fed'. Chen and Smith (1979) delivered the EtOH in a saccharin solution to treated animals, but controls only received water.…”
Section: Details Of Control Groupsmentioning
confidence: 99%
“…Interestingly, two studies (Lan et al 2009, Sliwowska et al 2016 reported quite similar hormonal and maturational changes in their PAE and pair-fed offspring Animal studies are ordered based on the timing of alcohol exposure. *Key results are in alcohol-exposed offspring compared to non-exposed, isocaloric (where available) controls; a Tanner stage drawings (Marshall & Tanner 1969) were used to assess breast/pubic hair development in girls; b only adjusted means (no s.d.)…”
Section: Summary Of Studies Reporting On Female Reproductive Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely known that alcohol abuse produces a variety of medical, psycho-sociological and physiological disorders at different levels, including the reproductive system (Canteros et al 1995, Cebral et al 1997, 1998a,b, 2011, Lee et al 2010. Numerous studies have shown the deleterious effects of chronic heavy alcohol consumption on testicular function and spermatogenesis (Shayakhmetova et al 2013(Shayakhmetova et al , 2014, on testosterone serum levels (Salonen et al 1992, Muthusami & Chinnaswamy 2005, Lee et al 2010, Jensen et al 2014, Sliwowska et al 2016) and on hypothalamic-pituitary-testicular axis function (Cicero & Badger 1977, Dees et al 1990, Välimäki et al 1990, Salonen et al 1992, Zhang et al 2005. Clinical manifestations in alcoholic men include hypogonadism, testicular atrophy, feminization, sexual dysfunction (Van Thiel et al 1990, Van Heertum & Rossi 2017, infertility and delayed sexual maturation (Anderson et al 1989).…”
Section: Introductionmentioning
confidence: 99%